Kerukunan Umat Beragama sebagai Cita-cita Etis (Tinjauan Perspektif Etika Filosofis-Religius) - M Nur Prabowo S (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
This paper is a philosophical reflection and analysis by the writer, who is doing research on religious radicalism in Indonesia. The main idea is the principle of religious harmony as a social norm and ethical idealism. From the perspective of philosophical and religious ethics, the condition of harmonious diversity represents the social-good that should be manifested in ways that justified ethically as well. Theoritically, the norm of harmony contains etiquettes, rational consideration, and can be justified in terms of obligations and responsibilities, and in line with the principles of moderation.Keywords: Religious harmony, Ethics, Religion.